2018
DOI: 10.3390/nu10010106
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fatty Acids Alter Lipid Profiles and Induce Myocardial Dysfunction without Causing Metabolic Disorders in Mice

Abstract: Oversupply of bulk saturated fatty acids (SFA) induces metabolic disorders and myocardial dysfunction. We investigated whether, without causing metabolic disorders, the uptake of individual dietary SFA species alters lipid profiles and induces myocardial dysfunction. C57BL/6 mice were fed various customized long-chain SFA diets (40% caloric intake from SFA), including a beef tallow (HBD), cocoa butter (HCD), milk fat (HMD) and palm oil diet (HPD), for 6 months. An isocaloric fat diet, containing medium-chain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In general, we found upregulation of both n-3 and n-6 PUFA series contents, as well as increased contents of most individual PUFAs in the heart muscle of mice fed an HFD, with the exception of significantly downregulated EPA ( Table 2). This accumulation of specific PUFAs is consistent with previous studies; for example, mitochondrial phospholipids in hearts were shown to readily incorporate dietary DHA [89] or ARA [88]. One possible explanation for the elevated levels of long-chain PUFAs (ARA, DHA, etc.)…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, we found upregulation of both n-3 and n-6 PUFA series contents, as well as increased contents of most individual PUFAs in the heart muscle of mice fed an HFD, with the exception of significantly downregulated EPA ( Table 2). This accumulation of specific PUFAs is consistent with previous studies; for example, mitochondrial phospholipids in hearts were shown to readily incorporate dietary DHA [89] or ARA [88]. One possible explanation for the elevated levels of long-chain PUFAs (ARA, DHA, etc.)…”
Section: Discussionsupporting
confidence: 91%
“…Although there are some studies investigating the effects of dietary fat on rodent cardiac functions, most of them do not report specific FA profiles or do so only for total lipid FA profiles in heart tissue [50,53,72]. Alternatively, only FA profiles for one selected group of lipid species are presented [86][87][88]. Some studies focused mostly on SFAs and MUFAs [51], while PUFAs have not been widely reported.…”
Section: Discussionmentioning
confidence: 99%
“…The intake of HFD has been associated with the development of metabolic diseases and to the onset of neurodegenerative diseases [34][35][36][37][38]. These types of diets harbor PA as one of the main saturated fatty acids [39][40][41]. Although several mechanisms regarding its effects have been characterized in peripheral tissues [10][11][12][13], it remains poorly understood the neuronal responses activated by PA.…”
Section: Discussionmentioning
confidence: 99%
“…The intake of HFD has been associated with the development of metabolic diseases and to the onset of neurodegenerative diseases [34][35][36][37][38]. These types of diets harbor PA as one of the main saturated fatty acids [39][40][41]. Although several mechanisms regarding its effects have been characterized in peripheral tissues [10][11][12][13], it remains poorly understood the neuronal responses activated by PA.…”
Section: Discussionmentioning
confidence: 99%